Outlook on human-centric manufacturing towards Industry 5.0. (January 2022) - Lu, Yuqian; Zheng, Hao; Chand, Saahil; Xia, Wanqing; Liu, Zengkun; Xu, Xun; Wang, Lihui; Qin, Zhaojun; Bao, Jinsong
Abstract: The recent shift to wellbeing, sustainability, and resilience under Industry 5.0 has prompted formal discussions that manufacturing should be human-centric – placing the wellbeing of industry workers at the center of manufacturing processes, instead of system-centric – only driven by efficiency and quality improvement and cost reduction. However, there is a lack of shared understanding of the essence of human-centric manufacturing, though significant research efforts exist in enhancing the physical and cognitive wellbeing of operators. Therefore, this position paper presents our arguments on the concept, needs, reference model, enabling technologies and system frameworks of human-centric manufacturing, providing a relatable vision and research agenda for future work in human-centric manufacturing systems. We believe human-centric manufacturing should ultimately address human needs defined in an Industrial Human Needs Pyramid – from basic needs of safety and health to the highest level of esteem and self-actualization. In parallel, human-machine relationships will change following a 5C evolution map – from current Coexistence, Cooperation and Collaboration to future Compassion and Coevolution. As such, human-centric manufacturing systems need to have bi-directional empathy, proactive communication and collaborative intelligence for establishing trustworthy human-machine coevolution relationships, thereby leading to high-performance human-machine teams. It is suggested that future research focus should be on developing transparent, trustworthy and quantifiable technologies that provide a rewarding working environment driven by real-world needs. Highlights: Defined the concept of human-centric manufacturing and proposed a 5-level Industrial Human Needs Pyramid that defines humans needs in manufacturing. Proposeda 5C evolution journey of human-machine relationship that ultimately targets Compassion and Coevolution, beyond current Coexistence, Cooperation and Collaboration. Discussed the enabling technologies for achieving human-centric manufacturing. Proposed human-centric manufacturing system framework and human-centric human-robot collaboration framework. Discussed the grand challenges for achieving human-centric manufacturing.